1995
DOI: 10.1111/j.1365-2672.1995.tb03164.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of Helicobacter pylori NCTC 11637 by organic acids and lactic acid bacteria

Abstract: In this study the effects of both pH and organic acids on Helicobacter pylori NCTC 11637 were tested. Lactobacillus acidophilus, Lact. casei, Lact. bulgaricus, Pediococcus pentosaceus and Bifidobacterium bifidus were assayed for their lactic acid production, pH and inhibition of H. pylori growth. A standard antimicrobial plate well diffusion assay was employed to examine inhibitory effects. Lactic, acetic and hydrochloric acids demonstrated inhibition of H. pylori growth in a concentration-dependent manner wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
132
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(149 citation statements)
references
References 11 publications
11
132
0
6
Order By: Relevance
“…The results of MIC, MBC, and killing kinetic assays showed the effective anti-H. pylori abilities of PA and indicated the therapeutic effect of PA against clinical antibiotic-resistant strains. For the acid MIC experiment, pH 5.3 was employed, since H. pylori usually lives under mildly acidic conditions between gastric epithelial cells and the gastric mucosa with pH ranging from 5.3 to 6.9 (21,22). A potent antibacterial activity of PA was found even in low-pH environments.…”
Section: Discussionmentioning
confidence: 99%
“…The results of MIC, MBC, and killing kinetic assays showed the effective anti-H. pylori abilities of PA and indicated the therapeutic effect of PA against clinical antibiotic-resistant strains. For the acid MIC experiment, pH 5.3 was employed, since H. pylori usually lives under mildly acidic conditions between gastric epithelial cells and the gastric mucosa with pH ranging from 5.3 to 6.9 (21,22). A potent antibacterial activity of PA was found even in low-pH environments.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential benefits of ingesting probiotics is their antagonistic effect against harmful microorganisms (Midolo et al 1995). There are innumerable articles that list the effects of probiotics in decreasing gastrointestinal disorder, intestinal bowel syndrome, diarrhea, lactose intolerance etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Lactobacillus rhamnosus GG, Lactobacillus reuteri, Lactobacillus casei and Lactococcus lactis can shorten the duration of diarrhea by approximately 1 day (Kaila et al, 1992;Shornikova et al, 1997;Sugita and Togawa, 1994). Lactobacilli have been shown to be antagonistic to Helicobacter pylori which are implicated in chronic gastritis, stomach carcinoma, gastric and duodenal ulcers and in gnotobiotic murine models (Aiba et al, 1998;Kabir et al, 1997;Midolo et al, 1995).…”
mentioning
confidence: 99%